LITERASI NEUROSAINS GURU SAINS PRA-JABATAN: NEUROMI DAN PEMAHAMAN PROFESIONAL TENTANG PEMBELAJARAN DAN MEMORI - Eryandi Ray; Dasrizal Dahlan; Rosniati Hakim; Ahmad Lahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teachers' lack of understanding of neuroscience in learning has led to the emergence of neuromitos, which are misconceptions in distinguishing facts and myths related to brain function in the learning process. This study aims to (1) elaborate neuromitos in education and (2) explain the relationship between neuroscience literacy and professional understanding of learning and memory. The method used is descriptive qualitative research with a literature study approach. The results show that (1) lack of knowledge and high interest in neuroscience, without proper understanding, as well as inappropriate teaching strategies, contribute to the spread of neuromitos, and (2) teachers who have good neuroscience literacy and master effective teaching techniques are better able to recognize and eliminate neuromitos and implement evidence-based learning strategies.